2015
DOI: 10.1142/s0218810415500045
|View full text |Cite
|
Sign up to set email alerts
|

The Greek Version of the Hand20 Questionnaire: Crosscultural Translation, Reliability and Construct Validity

Abstract: The English version of Hand20 questionnaire was translated into Greek and cultural adaptation was performed. The validity was assessed in 134 patients with a variety of upper limb disorders. A comparison of Hand20 and DASH was also performed. All patients completed EQ-5D, Hand20 and DASH questionnaire. Test-retest reliability was assessed in a subgroup of 37 patients. We assessed the convergent validity of Hand20 by correlating its scores to DASH and EQ-5D scores. We also compared the completeness of Hand20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Given the increasing elderly population in the world, there is a growing need for tools to assess the healthrelated quality of life of older people. One of the most momentous advantages of the Hand20 questionnaire is that it can be easily completed by individuals over the age of 65 [5,8]. In our study, similar findings were obtained.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Given the increasing elderly population in the world, there is a growing need for tools to assess the healthrelated quality of life of older people. One of the most momentous advantages of the Hand20 questionnaire is that it can be easily completed by individuals over the age of 65 [5,8]. In our study, similar findings were obtained.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, Cronbach's alpha value for Hand20 was 0.933, demonstrating excellent internal consistency. As far as it is known, only the Greek version of the translated Hand20 has been published, and the authors reported the Cronbach's alpha coefficient for their version as 0.956 [5]. In the original version, Suzuki et al reported the Cronbach's alpha value as 0.973 for the 20 items [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations